MANAGEMENT STRATEGY FOR FISH PROCESSING UNIT (UPI) IN SIHENE'ASI VILLAGE LAHEWA SUBDISTRICT, NORTH NIAS REGENCY - Jansen Daeli; Sukendi Sukendi; Dewita Dewita (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This study aims to formulate a management strategy for the fish processing unit inSihene'asi Village, Lahewa District, North Nias Regency. The research was conductedfrom 21 December 2020 to 23 January 2021. The research was conducted using aqualitative approach through survey methods and direct observation in the field. Primarydata collection was carried out through observation and in-depth interviews with astructured questionnaire instrument. Secondary data were obtained from related agenciesin this study. The analysis used in this research is descriptive analysis method and SWOTanalysis to determine the appropriate management strategy. The results of the SWOTanalysis show that the priority strategy related to the management of the fish processingunit is to support an aggressive strategy, a strategy that is made by utilizing all strengths toseize and take advantage of the greatest possible opportunities. The management strategiesof the fish processing unit in Sihene'asi Village are: 1) Maximizing the use of rawmaterials in meeting market demand through cooperation between UPI managers, 2)Maximizing traditional processing technology appropriately in order to maintain the tasteimage of fishery products and 3) Developing a group institutional system. fish processingby cooperating with the government / private sector.